DIGITAL ECONOMY AND BLOCKCHAIN ON THE INDONESIAN ECONOMY IN THE FUTURE - Lamria Novalita; Mintarsih Mintarsih; Rainier Wardhana Hardjanto (Faculty of Economics and Business Universitas Pelita Harapan, 2022)
This study aimed to see the opportunities for the development of the digital economy in the future. The Industrial Revolution 4.0 has brought changes to human life. Not only in technological advancements but also in changing mindsets/paradigms and bringing economic, business and digital investment opportunities. Change is inevitable, now or later the development of science and technology (science and technology) will occur, humans must adapt to changing times. The development of the digital economy is not only based on things that are visible to the naked eye, but also things related to the metaverse and based on big data, artificial intelligence (AI), cloud computing, and advanced robotics. This study also uses a SWOT analysis as an analytical tool to obtain comprehensive results regarding the opportunities of the digital economy in the future. The method used in this research is a qualitative method using a descriptive approach and literature study. The results of the study show that the digital economy will continue to develop along with the times. Various aspects related to the digital economy will continue to develop, such as banking laws and policies. In time, it is possible that digital currency (cryptocurrency) used as a medium of exchange in trade.